2003
DOI: 10.1038/sj.ijo.0802204
|View full text |Cite
|
Sign up to set email alerts
|

Prospective association between obesity and depression: evidence from the Alameda County Study

Abstract: OBJECTIVE:To examine the temporal relation between obesity and depression to determine if each constitutes a risk factor for the other. DESIGN: A two-wave, 5-y-observational study with all measures at both times. SUBJECTS: A total of 2123 subjects, 50 y of age and older, who participated in the 1994 and 1999 waves of the Alameda County Study. MEASUREMENTS: Obesity defined as body mass index (BMI)X30. Depression assessed using DSM-IV symptom criteria for major depressive episodes. Covariates include indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
387
7
12

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(450 citation statements)
references
References 37 publications
37
387
7
12
Order By: Relevance
“…38 A recent study showed that depressed adolescents were at increased risk of obesity in a 1-year follow-up. 14 This study gives the assumption, similarly to Roberts et al, 15,17,18 that obesity predicts later depression. A thin and beautiful body is idealized among adolescents, especially among girls.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…38 A recent study showed that depressed adolescents were at increased risk of obesity in a 1-year follow-up. 14 This study gives the assumption, similarly to Roberts et al, 15,17,18 that obesity predicts later depression. A thin and beautiful body is idealized among adolescents, especially among girls.…”
Section: Discussionmentioning
confidence: 61%
“…One of the few follow-up studies with prospectively collected data found that obesity predicted depression in a 1-year followup, when other variables were controlled. 15 Roberts et al 17 found in a two-wave, 5-year observational study of 2123 subjects 50 years and older from the Alameda County Study data, that obesity at baseline was associated with increased risk of depression 5 years later, and that depression did not increase the risk of future obesity. Another recent study investigating the association between obesity and eight indicators of mental health using community residents 50 years and older showed that obese subjects were at increased risk for depression 5 years later.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Earlier studies failed to detect significant associations between the two disorders [3][4][5] while more recent studies have reported a relation between obesity and depression in some samples. 6,7 Literature reviews 1,8 note that discrepant findings probably reflect the demographic heterogeneity of samples across previously studied and the lack of population-based samples. The lack of population-based studies is especially problematic for investigating potential ethnic differences in the association between depression and obesity given the ethnic disparities of obesity in the US.…”
Section: Introductionmentioning
confidence: 99%
“…15 On the other hand, in the Great Smoky Mountain Study, chronically obese girls assessed over an 8-year period were at increased risk of oppositional defiant disorder but not anxiety or depressive disorder; however, outcomes were assessed in adolescence. 16 Evidence that obesity may be implicated in the etiology of clinical depression in women is based on prospective data drawn from adults over age 50 in the Alameda County Study: 17 baseline obesity (BMI X30) significantly increased the odds of incident DSM-IV major depression by 79% 5 years later after adjustment for potential confounders that included measures of status attributes, personal and social resources and stressors. Because that association did not differ significantly across gender, however, separate odds were not given for men and women.…”
Section: Introductionmentioning
confidence: 99%